Women's education and politics of gender - Chakraborty Uttara; Das Banimanjari (Calcutta Bethune College, 2004)
The first part of the book has ten essays on different facets of women's education and the second part of the book deals with the politics of gender.
Published on the occasion of the celebration of 125th year of Bethune College
Keywords: India; Women; Women-education; Women-political activity